The centrality of 'between' in intellectual entrepreneurship - Ariane Berthoin Antal (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2004)
A great deal of intellectual entrepreneurship happens between institutions. Between institutions in the dual sense of the term: institutions as organizations and institutions as conventions. Ideas and the energy to take them forward are often born when people from different organizations come together, ideas that might not fit within one institution alone. And the introduction of new ideas often involves pushing institutions as conventions aside, creating new space BETWEEN existing institutions for the different idea to emerge. The article explores the example of a business- and-research venture, CHOICE mobilitätsproviding GmbH, to illustrate the importance of multiple types of BETWEEN and their significance for organizational learning. – – In der modernen Wirtschaft und Gesellschaft ist Wissen die wichtigste erneuerbare Ressource. Welche Rolle spielen Institutionen bei der Generierung von Wissen und dessen Umsetzung in Innovationen? Findet wissensbasiertes unternehmerisches Denken und Handeln innerhalb von Institutionen oder eher außerhalb von Institutionen statt? In diesem Beitrag wird die Bedeutung von Räumen und Zeiten zwischen Institutionen hervorgehoben und zwar im doppelten Sinn: Institutionen als Organisationen und Institutionen als Konventionen. Anhand des Beispiels der CHOICE mobilitätsproviding GmbH, einem Unternehmen zwischen Wirtschaft und Wissenschaft, werden einige Zwischen-Institutionen dargestellt und ihre Bedeutung für das Organisationslernen erläutert.
Keywords: 300; Wissen; Unternehmer; Organisation; Institutionalismus; Lernende Organisation